Serologic evidence of zoonotic alphaviruses in humans from an indigenous community in the Peruvian Amazon - Pérez, Jocelyn G. (2019)
This research was supported by a grant fromSENACYT FID 16-201 to J. P. C. and A. V., Secretar ́ıa Nacional deCiencia y Tecnolog ́ıa from Panama; by the grant for neglected dis-eases studies in Panama 1.11.1.3.703.01.55.120 from the Ministry ofEconomy and Finance of Panama to J. P. C. and A. V.; and byERANet17/HLH-0271. Scott Weaver also supported this studythrough the World Reference Center for Emerging Viruses and Arbo-viruses, NIH grant R24AI120942. Dr. Lescano is sponsored by thetraining grant D43 TW007393 awarded by the Fogarty InternationalCenter of the US National Institutes of Health. J. L. M. is a doctoralcandidate studying an Epidemiological Research Doctorate at Uni-versidad Peruana Cayetano Heredia under FONDECYT/CIENCIAC-TIVA scholarship EF033-235-2015 and also supported by traininggrant D43 TW007393. A. V. is a member of the Sistema Nacional deInvestigaci ́on de Panam ́a (SNI),SENACYT.E.S. was supportedby theSpanish Ministerio de Ciencia Innovaci ́on y Universidades (MICINN)through a Ramon y Cajal agreement (RYC-2016-21120).